VARIABILITAS MUSIMAN CLOUD GROUND LIGHTNING DAN KAITANNYA DENGAN POLA HUJAN DI WILAYAH JAWA (SUDI KASUS BANDUNG DAN SEMARANG) - Septiadi, Deni; Tjasyono, Bayong (Bumi Lestari; Vol 11 No 1 (2011), 2011)
The objective of this paper is to describe the relationship between CG (Cloud Ground) lightning observation data to rainfall in Java region. CG lightning data obtained by using Lightning Detector that is able to track low frequency of radio signals from electrical processes lightning discharge and installed in Bandung Geophysics Station. For better resolution, data is limited within a radius of 10 km square of study area. The results showed a strong relationships between CG and rainfall (r2 = 0.9) and the dominance of CG+ compared with CG- throughout the season with a peak in the MAM (March-April-May) for Bandung (40.6%) and DJF ( December-January-February) for Semarang (48%). Understanding of the peculiarities of lightning activity will provide important information in the structure, the growth of clouds, atmospheric labilitas or as a warning extreme weather. Therefore, it is possible to utilize CG lightning as predictors for rainfall prediction.
Keywords: CG, Lightning, MAM, DJF, predictor